Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 22 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Cyprinus carpio Linnaeus, 1758", "Country is India" ] } The dataset includes 22 records from 5 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0006821-160803222355964/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences